1998
DOI: 10.1177/095624789801000102
|View full text |Cite
|
Sign up to set email alerts
|

Taking advantage of rural assets as a coping strategy for the urban poor: the case of ruralurban interrelations in Botswana

Abstract: This paper describes the importance of rural-urban links for many of the inhabitants of Botswana's cities. This is described in more detail for Old Naledi, a low-cost, self help settlement in Botswana's capital, Gaborone. A third of all households there own cattle, half retain land in the village from which they come and the proportion of households with such rural assets does not decline with people's length of stay in the city. These rural assets are valued both in monetary and social terms and serve as a va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Other evidence from rural settings suggests that 40% of rural households send maize to family and friends in nearby towns or cities (Djurfeldt 2015). These rural food linkages received by urban households have been shown to play a significant role in promoting household food security, even more than urban households' engagement in agricultural production (Krüger 1998). Frayne (2004) found that urban households in Windhoek, Namibia with limited social connections to rural areas were the most vulnerable to hunger, whereas those with active and robust ties to rural households regularly received transfers of food that made a considerable contribution to their overall household food budget.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Other evidence from rural settings suggests that 40% of rural households send maize to family and friends in nearby towns or cities (Djurfeldt 2015). These rural food linkages received by urban households have been shown to play a significant role in promoting household food security, even more than urban households' engagement in agricultural production (Krüger 1998). Frayne (2004) found that urban households in Windhoek, Namibia with limited social connections to rural areas were the most vulnerable to hunger, whereas those with active and robust ties to rural households regularly received transfers of food that made a considerable contribution to their overall household food budget.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Studies have previously shown that many people in Gaborone maintain strong links to their ancestral villages and their respective communities (Krüger, 1998;Lesetedi, 2003), which are increasingly strained by the impact of water shortage. A woman participant said:…”
Section: Social Exclusion and Embarrassmentmentioning
confidence: 99%